Sugar-alcohol@ZIF nanocomposites display suppressed phase-change temperatures. Issue 45 (16th November 2020) - Hackl, Lukas; Hsu, Chih-Hao; Gordon, Madeleine P.; Chou, Kelly; Ma, Canghai; Kolaczkowski, Matthew; Anderson, Christopher L.; Liu, Yi-Sheng; Guo, Jinghua; Ercius, Peter; Urban, Jeffrey J.
Abstract : The synthesis and characterization of phase change materials infused into metal–organic framework crystals to demonstrate high latent heats with suppressed phase change temperatures. Abstract : For the sake of water and energy conservation, development of latent heat cooling and thermal storage systems that minimize water consumption and operate with higher efficacy than their water-driven counterparts is a crucial task. Phase change materials (PCMs) present a potential solution, but their integration into real-world systems abounds with scientific challenges such as material toxicity, flammability, low thermal performance and lack of tunable phase-change temperatures. In this study we report on a first-in-class nanocomposite PCM that leverages non-flammable, non-toxic, high latent heat sugar alcohols (SAs) encapsulated within easy-to-synthesize zeolitic imidazolate framework (ZIF) crystals. We also outline a practical route for surface functionalization with hydrophilic and hydrophobic moieties. The SA@ZIF composites display suppressed phase-change temperatures which, together with alterable surface functionality, broadens their applicability to a plethora of working environments. Direct synthesis of the SA@ZIF composite generates nanoconfined SAs with phase-change temperatures as low as 19.8 °C and latent heats as high as 285 J g −1 . This nanoconfinement-induced thermal phenomenon is conserved even after functionalization of the SA@ZIF crystal surface. We believe this study will lay the groundwork as a platform for next generation high performing, tunable PCMs to aid in the realization of waterless cooling systems.